2019
DOI: 10.5603/fhc.a2019.0008
|View full text |Cite
|
Sign up to set email alerts
|

The immunoreactivity of TGF-b1 in non-alcoholic fatty liver disease

Abstract: Introduction. Non-alcoholic fatty liver disease (NAFLD) is a common chronic liver disease which becomes a rapidly growing health problem in the Western countries. The development of the disease is most often connected to obesity. NAFLD is also considered as the hepatic manifestation of metabolic syndrome. Transforming growth factor b1 (TGF-b1) plays an important role in the pathogenesis of liver fibrosis, being involved in activation of hepatic stellate cells, stimulation of collagen gene transcription, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Other organs are also affected by TGF beta 1. TGF beta 1 affects changes in the structure of the liver, so the use of immunohistochemical diagnostics of the degree of TGF beta 1 expression is proposed to assess the degree of liver fibrosis [22].…”
Section: Resultsmentioning
confidence: 99%
“…Other organs are also affected by TGF beta 1. TGF beta 1 affects changes in the structure of the liver, so the use of immunohistochemical diagnostics of the degree of TGF beta 1 expression is proposed to assess the degree of liver fibrosis [22].…”
Section: Resultsmentioning
confidence: 99%
“…This reported correlation is compatible with some previous findings demonstrated that serum level of HA was positively associated with both serum TFG-β1 and TGF-β1 expression in the selected consecutive liver compartments. 46 , 47 In addition, the expression of TGF-β1 was reported to be closely associated to liver fibrosis and evaluation of serum TGF-β1 levels may contribute to the diagnosis of liver fibrosis. 48 We reported also the existence of positive significant correlation between serum HA and liver stiffness, a result seems in accordance with the findings of other authors who reported that serum HA levels are related to stage of fibrosis and degree of necroinflammation.…”
Section: Discussionmentioning
confidence: 99%